If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6m+2-4m=2(-m+2)
We move all terms to the left:
6m+2-4m-(2(-m+2))=0
We add all the numbers together, and all the variables
6m-4m-(2(-1m+2))+2=0
We add all the numbers together, and all the variables
2m-(2(-1m+2))+2=0
We calculate terms in parentheses: -(2(-1m+2)), so:We get rid of parentheses
2(-1m+2)
We multiply parentheses
-2m+4
Back to the equation:
-(-2m+4)
2m+2m-4+2=0
We add all the numbers together, and all the variables
4m-2=0
We move all terms containing m to the left, all other terms to the right
4m=2
m=2/4
m=1/2
| 6m+2-4m=2(-m+2) | | 6m+2-4m=2(-m+2) | | 6m+2-4m=2(-m+2) | | 6m+2-4m=2(-m+2) | | 6y+8=5y+10 | | 6y+8=5y+10 | | 6y+8=5y+10 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | x4+-3x2-10=0 | | y-11=3y-11 | | w/0.197=7.8 | | 5x10=-44-4x | | –k=–217 | | 7e+3.3=0.3 | | 3-6y=144 | | -6x^2-16x-8=0 | | –12=3(d+9) | | –12=3(d+9) | | –12=3(d+9) | | 1/3x−9=15 | | 6x+13=36 | | 6x+13=36 | | (12/x)=(-22/(x-5) | | 3*11x=4 |